Rhythm - Jane Beethoven; Rosanne Emery; Synía Carroll-McQuillan (Music magic video library, 1995)
Viewers are introduced to rhythm through a variety of visual and aural techniques - - Discover rhythm as it is found in our every day environment - - Hear the famous Kodo drummers from Japan - - Hear percussionists from Africa and the United States - - See famed juggler, Michael Moschen, create rhythm patterns by bouncing balls inside a piece of sculpture.